Are Age-related Changes Evident in the Active and/or Passive Components of Pelvic Floor Muscle Force Outcomes in Nulliparous Women? - Semmen, Mahin (Université d'Ottawa / University of Ottawa, 2018)
Background: Age-related changes in pelvic floor muscle (PFM) biomechanics may contribute to urinary incontinence in older women; however, empirical evidence is scant. Purpose: This study aimed to understand the age-related changes in the biomechanical properties of the PFMs in women with no major risk factors for urinary incontinence. Methods: Thirty-three nulliparous women (20-64 years) were recruited to study active force, rate of force development, endurance, resistance to passive stretch and stiffness properties of the PFMs using an automated dynamometer. Separate regression analyses were performed to investigate the relationship between age and each outcome measure. Results: No significant relationships were observed between age and any of the outcome measures. Conclusion: The findings from this study do not support the presence of any age-related changes in PFM mechanics among women aged 20-64. Recruiting women over the age of 65 may be essential to detect age-related changes in PFM biomechanics in nulliparous women.
Keywords: aging; pelvic floor muscles; active force; passive force